How black tea pigment theaflavin dyes chicken eggs: Binding affinity study of theaflavin with ovalbumin. (15th January 2020) - Wu, Di; Mei, Sen; Duan, Ran; Geng, Fang; Wu, Wanxia; Li, Xiang; Cheng, Lei; Wang, Chengtao
Abstract: Theaflavin (TF), which is the key pigment in black tea, is a health-promoting food component with beneficial effects on humans. However, the interactions by which these effects are transferred and exerted into protein-rich foods are unclear. Here, egg ovalbumin (OVA) was selected as a representative dietary protein to ascertain their binding mechanism. Steady-state, time-resolved fluorescence and isothermal titration calorimetric results showed that TF can interact well with OVA with an affinity magnitude of 10 4 . The noncovalent binding was mainly driven by hydrophobic interaction and hydrogen bonds. Structural analysis displayed that the TF binding pocket significantly overlapped with one of the surrounding specific IgE-binding epitopes, thereby causing a subtle structural adjustment on the secondary conformation of OVA. The biological complexation model that was delineated here will help understand how black tea dyes egg white in tea egg products and for the development of protein-rich carriers in functional foods.